New Policies on Basic Quality Conditions and Their Implications for the Licensing Process of a Public Institute in Ancash - Robles Perez, Zandra Raquel (2024)
The general objective of this scientific study was to explain to what extent the new policies on basic quality conditions affect the licensing process of a public institute in Ancash. The method used was the hypothetical deductive method, establishing hypotheses and testing them by statistical methods, with a quantitative approach, a non-experimental correlational causal research design with a cross-sectional approach, applied to a sample of 42 workers. The survey was used as a technique and two validated and reliable questionnaires were used as instruments, each related to its respective variable. The conclusion was that a Nagelkerke R^2 of 0.569 was obtained with a sig. = 0.000<0.01; which indicates that the new policies of basic quality conditions influence 56.9% in the licensing process of a public institute in Ancash in 2024, in addition the highest intersection value is located in regular with 45.2%, therefore, it is favorable to continue executing with the respective monitoring to achieve the proposed goals.